2020
DOI: 10.21608/dsu.2020.25987.1031
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 immunohistochemical expression in DMBA – induced oral squamous cell carcinoma treated with different thymoquinone preparations

Abstract: Introduction: The X-ray repair cross-complementing 1 (XRCC1) enzyme plays an important role in the DNA repair pathway. XRCC1 polymorphism increased the risk of human oral squamous cell carcinoma. Loading of thymoquinone on gold nanoparticles as a drug carrier, had revealed a superior anti-cancer effect as a chemotherapeutic agent in DMBA-induced OSCC. Aim of the work: This study aimed to evaluate the expression of DNA repair enzyme X-ray repair cross-complementing 1 (XRCC1) following treatment of induced oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 25 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown that TQ impacts the oxidative stress environment of cancer cells, which may contribute to its chemoprevention and cytotoxicity in SCC 5,6,12,16 . As early as 1999, Badary et al investigated the effects of TQ on benzo(a)pyrene (BP)‐induced forestomach squamous cell tumors in mice 12 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that TQ impacts the oxidative stress environment of cancer cells, which may contribute to its chemoprevention and cytotoxicity in SCC 5,6,12,16 . As early as 1999, Badary et al investigated the effects of TQ on benzo(a)pyrene (BP)‐induced forestomach squamous cell tumors in mice 12 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair enzymes such as XRCC1 are therefore integral to mitigating oxidative stress and subsequent carcinogenesis 77 . Amer et al's work in DMBA‐induced buccal pouch SCC in Syrian golden hamsters demonstrated that topical and intraperitoneal injection of TQ‐GNps resulted in cytotoxicity associated with an increase in mRNA and protein expression of XRCC1 5,6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations